Analisis Kepuasan Pengguna Pelayanan Aplikasi BRImo pada Bank BRI KCP Sudirman - Junanda, Ogie; Imal Alfresi, Aminullah (MDP Student Conference, 2024)
The rapid development of technology has significantly impacted the banking sector, particularly in Indonesia. Bank Rakyat Indonesia (BRI), a government-owned bank, offers digital banking services through the BRImo application. This study employs the End User Computing Satisfaction (EUCS) method to assess user satisfaction with BRImo at BRI KCP Sudirman. The analysis results using SPSS version 25 indicate a high level of satisfaction across content, accuracy, format, ease of use, and timeliness variables. This positive evaluation suggests that BRImo meets user expectations, provides a satisfying experience, and is considered adequate in delivering information and services. These findings serve as a foundation for BRI to enhance the quality of information technology services and further improve customer satisfaction.